INFLUENCE OF MIGRATION PROCESSES ON THE FORMATION OF INTELLECTUAL POTENTIAL - Маринчак, Лілія Романівна (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2024)
The article examines the concept of intellectual potential and its importance for the country's development, evaluates the impact of migration processes on the formation and use of intellectual capital, determines the consequences of migration for countries from the point of view of intellectual use, and suggests ways of preserving and effectively managing the intellectual potential of Ukraine in the context of the loss of part of the human capital as a result of the war. It is noted that in the modern era of high technologies and digital transformation, the country's intellectual potential plays an extremely important role in the development of modern society. The concept of a country's intellectual capital is defined as a set of intangible resources that influence a country's innovativeness, creativity, and overall ability to produce and use knowledge to achieve economic growth and competitiveness. The components of intellectual capital, which are education and science, technologies, intellectual property, human resources, the economic system, cultural and creative potential, the ability to adapt and innovate, were studied. The significant influence of migration processes on the intellectual potential of the country is substantiated and the consequences of migration, which can be both positive and negative, are determined. In particular, for countries that export human capital, migration can lead to a loss of intellectual potential. However, for migrant-importing countries, this can become a source of new talents and intellectual capital, as they receive trained specialists who, after an adaptation period, are ready to work and multiply intellectual values in new conditions. The current situation in Ukraine proves that in the conditions of war and emergency situations, external and internal migration processes are intensified, resulting in significant losses of intellectual capital and potential. Emphasis is placed on the importance of managing intellectual potential in conditions of migration for its preservation and effective intellectual use. To achieve this goal, it is necessary to develop a policy aimed at attracting talented specialists, ensuring their rights and opportunities for professional and personal development. Directions for preserving and multiplying intellectual potential through the creation of a stimulating environment for scientific research development, support of educational programs and projects, all kinds of support for innovation and technological development are proposed. For the effective management of intellectual potential in conditions of migration, it is also important to develop mechanisms for the exchange of knowledge and experience, as well as to attract experts from abroad for joint work and implementation of projects.